2021
DOI: 10.1002/1348-9585.12269
|View full text |Cite
|
Sign up to set email alerts
|

Dentists have a high occupational risk of neck disorders with impact on somatosensory function and neck mobility

Abstract: Objectives Musculoskeletal disorders (MSDs) in the neck and shoulder region may be associated with significant impairment of quality of life and well‐being. The study was to determine the prevalence of painful MSDs in Chinese dentists and evaluate somatosensory function and neck mobility compared with non‐dental professional controls. Methods One hundred dentists (age: 36.5 ± 9.8 years) and 102 controls (age: 36.2 ± 10.0 years) were recruited between September 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Similar to the findings of the present study on opium smokers, previous studies have also found that dentists who work for several hours a day in harmful positions are at risk of developing various types of neck musculoskeletal disorders [ 49 , 50 ]. Prolonged sitting in non-ergonomic positions has a proven correlation with neck pain.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the findings of the present study on opium smokers, previous studies have also found that dentists who work for several hours a day in harmful positions are at risk of developing various types of neck musculoskeletal disorders [ 49 , 50 ]. Prolonged sitting in non-ergonomic positions has a proven correlation with neck pain.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the participants in this study did not use a microscope and loupes to reflect the clinical practice of most dentists in Thailand. A study of the prevalence of painful MSDs in Chinese dentists indicated that ergonomic training courses and physical activity might be beneficial for dentists in alleviating or preventing MSDs 33 . Based on our findings, effective measures are required to prevent dentists from adopting compromised and harmful neck postures during endodontic treatment.…”
Section: Discussionmentioning
confidence: 61%
“…A study of the prevalence of painful MSDs in Chinese dentists indicated that ergonomic training courses and physical activity might be beneficial for dentists in alleviating or preventing MSDs. 33 Based on our findings, effective measures are required to prevent dentists from adopting compromised and harmful neck postures during endodontic treatment. Possible effective interventions may include the use of microscopes and loupes as well as an ergonomic training program.…”
Section: Oc Lt MI Tmc Frcmentioning
confidence: 84%
“…In addition, a similar relationship between the number of hours working at the computer and the higher occurrence of neck disability in office workers has been shown (33). Studies conducted on dentists and farmers have also confirmed the effect of harmful positions due to work-related posture with a higher probability of neck pain and disability (34,35). Considering that in the previous studies, there has been no correlation between neck pain and disability and FHP with the drug use duration (36), it seems that the causal relationship with opium smoking duration is strengthened.…”
Section: Discussionmentioning
confidence: 68%